MOLECULAR AND CHEMICAL THERAPEUTIC FEATURES OF URTICA SPECIES - AlShuwayeb, Mousa H.; Al-Khatib, Ahed J. (European Scientific Journal, ESJ, 2013)
The present review study was conducted to review the current understanding of molecular aspects of Urtica species. We refer to the most recent published articles addressing the therapeutic potential of this plant. A wide spectrum of diseases has been associated with Urtica species including cancer, arthritis, autoimmune diseases, diabetes, and fatigue. Some molecular mechanisms and chemical properties have been discussed. Taken together, studies have confirmed the beneficial effects of Urtica all over the world and understanding of the molecular mechanisms underlying the beneficial effects opens new horizon to understand new therapeutic options. The extracts of Urtica should be prepared based on separating effective ingredients for optimal therapeutic benefits.